The 1918 influenza pandemic in Montevideo: The southernmost capital city in the Americas - Cristina, Juan (Influenza Other Respir Viruses, 2019)
BACKGROUND: Few studies have addressed the impact and dynamics of the 1918‐1919 influenza pandemic in temperate regions of South America. OBJECTIVE: To identify key factors for influenza onset, spread, and mortality in Montevideo and Uruguay in 1918‐1919. METHODS: An analysis of official national records of the public health system of Uruguay was performed. RESULTS: From November to December of 1918 (spring), a total of 131 deaths due to influenza occurred in Montevideo and a total of 296 deaths accounted from July to September of 1919 (winter) in the same city. The total deaths attributed to influenza in Uruguay in 1918 and 1919 were 926 and 1089, respectively. In contrast, the mean annual mortality attributed to influenza in Uruguay from 1908 to 1917 was 50.9. A pattern of age‐shift in mortality in the two pandemic waves studied was observed. CONCLUSIONS: The results of studies revealed that Montevideo was first hit by the devastating second wave of the pandemic of 1918, arriving Montevideo at the end of the spring of that year. The third wave arrived by July 1919, in the winter season, and in the capital city was as severe as the second one.